Beam test results of STS prototype modules for the future accelerator experiments FAIR/CBM and NICA/MPD projects - Kharlamov Petr; Dementev Dmitrii; Shitenkov Mikhail (EPJ Web of Conferences, 2017)
High-energy heavy-ion collision experiments provide the unique possibility to create and investigate extreme states of strongly-interacted matter and address the fundamental aspects of QCD. The experimental investigation the QCD phase diagram would be a major breakthrough in our understanding of the properties of nuclear matter. The reconstruction of the charged particles created in the nuclear collisions, including the determination of their momenta, is the central detection task in high-energy heavy-ion experiments. It is taken up by the Silicon Tracking System in CBM@FAIR and by Inner Tracker in MPD@NICA currently under development. These experiments requires very fast and radiation hard detectors, a novel data read-out and analysis concept including free streaming front-end electronics. Thermal and beam tests of prototype detector modules for these tracking systems showed the stability of sensors and readout electronics operation.